Dirty nevus due to fear of malignant degeneration. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Case report. A 15-year-old girl asked to assess a nevus of the neck, responsible for paresthesias in recent times. Her family history was negative for melanoma and her personal history did not highlight disorders responsible for immunosuppression. The girl presented about twenty 1-4 mm in size acquired melanocytic nevi on her head, torso and limbs and had a phototype suitable for latitude. Physical examination showed in her right cervical region a nevus of about 4 mm overall covered with scales that also affected the normal skin around the nevus (Fig. 1). Dermoscopy (Fig. 3) showed the scales as well as a cobblestone and globular pattern. After the girl admitted to not wash the area because of fear of degeneration of the nevus, the scales were removed with cotton wool soaked in soapy solution (Fig. 2), leading to the diagnosis of dirty nevus.